Mechanical and physical analysis of starch-gelatin edible film incorporated with garlic oil for food packaging - Rashid, Nurul Azera (2018)
Edible films were prepared from the mixture of partially hydrolyzed rice starch. Composite films with ratio 1:1, 1:2, and 2:1 (ratio 1 equal to 5g) were prepared by combining rice starch and gelatin as protein material. Garlic oil (1%, 2% and 3%) was used as the antimicrobial agent while glycerol (2%, 2.5% and 3%) incorporated in the films as antimicrobial agent and plasticizer respectively. The edible films produced were characterized for film thickness, tensile strength (TS), percentage elongation at break (%E), water vapor permeability (WVP), water solubility and antimicrobial activity test. Microorganism used are Escherichia coli which are negative gram bacteria. Bacterial strain was obtained from laboratory and inoculation and growth of the bacteria was done in the nutrient agar plate by using diffusion method. Garlic oil was used as the antimicrobial agent as it contains active compound which has potential to inhibit the growth of tested bacteria. Garlic oil was prepared using hydro-distillation method. Individual performance either starch-based only or protein-based only were reported to have many weaknesses. Research shows that starch-based film brittle while gelatin-based film too sticky. Composite based film will improve the performance in mechanical strength, water vapor permeability and other active film characteristic. Composite film ratio 1:2 gave the highest TS (10 MPa) compared to others due to higher gelatin composition. Additional of glycerol also improved the film characterization performance. Composite film of ratio 1:2 also shows that EAB increases from 10% to 40% with addition glycerol. All tests performed on the starch-gelatin based films were aimed to produce an edible film that will have or partially have the same characteristic as synthetic plastic that were used in current market. This research also drives upon the environmentally issues of non-biodegradable waste disposal.